2004
DOI: 10.1007/s11745-004-1252-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of tocopherols and tocotrienols to rat ocular tissues after topical ophthalmic administration

Abstract: With increasing evidence suggesting the involvement of oxidative stress in various disorders and diseases, the role of antioxidants in vivo has received much attention. Chemically, tocopherols and tocotrienols are closely related; however, it has been observed that they have widely varying degrees of biological effectiveness. The present study has been carried out in an attempt to deepen our understanding of whether there is a significant difference in distribution between tocopherol and tocotrienol homologs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…The preparation of ocular tissue samples has been described previously. 15,27 Briefly, after a deep anesthesia was induced by an intraperitoneal injection of pentobarbital sodium (30 mg/kg), the mice were perfused with ice-cold phosphate-buffered saline (PBS; pH 7.4) from the left ventricle to wash out the blood; subsequently, the eyes were rapidly enucleated. For morphologic analyses, the enucleated eyes were immersed in fixatives, as described in later sections.…”
Section: Preparation Of Ocular Tissue Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of ocular tissue samples has been described previously. 15,27 Briefly, after a deep anesthesia was induced by an intraperitoneal injection of pentobarbital sodium (30 mg/kg), the mice were perfused with ice-cold phosphate-buffered saline (PBS; pH 7.4) from the left ventricle to wash out the blood; subsequently, the eyes were rapidly enucleated. For morphologic analyses, the enucleated eyes were immersed in fixatives, as described in later sections.…”
Section: Preparation Of Ocular Tissue Samplesmentioning
confidence: 99%
“…S1, online at http://www.iovs.org/ cgi/content/full/48/1/396/DC1). 14 ␣-Toc is the most abundant VE in vivo, 15 although plants and normal diets often contain a nearly equal or a higher amount of ␥-Toc. ␣-Toc transfer protein (␣-TTP), a cytosolic liver protein with a highly specific binding affinity for ␣-Toc, selectively transports ␣-Toc from the liver to the blood stream 16 ; thus, the presence of ␣-TTP is thought to be the reason for such a high bioavailability of ␣-Toc in vivo.…”
mentioning
confidence: 99%
“…Tocotrienols are isomers of vitamin E, located primarily in plants, with antioxidative (9), anti-tumor (10) and neuroprotective functions (11). Tocotrienols inhibit proliferation of breast cancer cells, show G1 phase retardation and can promote cell apoptosis (12,13). However, to the best of our knowledge, the potential protective effect and underlying molecular mechanism of tocotrienol on SCI has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Tanito et al 18 also demonstrated increased concentration of α-tocopherol and α-tocopherol-3 in ocular tissues including neural retina after a 4-day application of 5μL pure α-tocopherol and α-tocopherol-3 (2.23±0.14 mg). However, topical α-tocopherol-3 was reported to reach much more drug concentration in ocular tissues than those detected with topical α-tocopherol.…”
Section: Discussionmentioning
confidence: 90%